Curriculum Strategy Based on Business and Industry in Vocational High School - Wijayanti, Putu Ranti; Akhiriyah, Umi; Khan, Habib-Ur-Rehman (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2022)
Business and Industry curriculum is program which is the content adopted from industial field. In line with the aimed of this study to turned up the teachers’ view of industry- based curriculum, found the challenges and the strategies of the implementation business and industrial organization. currriculum in vocational school. interveiw. Then interview as the instrument of this study, showed that the curriculum placed the students to a real experiece. Industry and business culture, dicipline character and the level of infrastructure found by the teachers as the problem. the programs which support the curriculum, were carried out. guest teacher programs, guest instructors, professional placement (PKL), industrial visit, internships and so on, belongs to the strategies for the implementation of the curriculum based on business and industryThe "Business and Industry" curriculum, rooted in industrial content, aims to provide students with real-world experience in vocational schools. This study explores teachers' perspectives on this industry-based curriculum, identifying challenges and implementation strategies. Teachers highlighted several obstacles, including adapting to industry and business culture, developing disciplined character in students, and dealing with infrastructure limitations. To address these challenges and effectively implement the curriculum, various strategies have been proposed. These include guest teacher programs, inviting guest instructors, professional placement (PKL), industrial visits, and internships. These initiatives are designed to support the curriculum and offer students practical exposure to the business and industrial world. The research methodology primarily relied on interviews to gather data from teachers regarding their views and experiences with the curriculum.